Thermal diffusivity measurement using photoacoustic and thermal lens techniques - Chin, Fanny Yee Ju (2000)
The open photoacoustic cell (OPC) technique was used for measuring thermal diffusivity of solid samples. It is based upon the measurement of the photoacoustic signal as a function of the modulation frequency in the region where the thermal diffusion length equals to the-sample thickness. The measurements were carried out at room temperature for samples metal, alloy, semiconductor, polymer and superconductor. The measured thermal diffusivity values for metal, semiconductor and polymer samples are in good agreement with the values reported previously by other researchers. The thermal diffusivity values of the AgxAu1-x alloys decrease from 1.48 cm2/s (pure Ag) to a minimum value at around x = 0.70 before increasing towards the value of 1.28 cm2/s (pure Au). In AuxCu(l00-x)07Ag(l00-x)O.3 alloy system, the thermal diffusivity values decrease with the increasing of the weight fraction x and reaching a minimum at around x = 90 composition. Then, the thermal diffusivity values tend to increase to the value of 1.28 cm2/s for the pure Au metal. For superconductor samples in the normal state, the measured thermal diffusivity decreases with the increase of Zn content in the BbPbo.6Sr2Ca2-xZnxCu30o system, However, the thermal diffusivity values increase with the increasing of Ba dopant in the Bi2Pbo.6Sr2Ca2-xBaxCu30o system. The OPC detection was also used to monitor the evaporation time of the liquid samples. The evaporation time for 10.60 mm3 of acetone, chloroform, methanol and ethanol samples were recorded as 236.7s, 578.8s, 436.2s and 869.2s respectively. The results also show that the liquid evaporation time is inversely proportional to the laser power. The laser beam power in the range of (2-16) m W was monitored by using OPC, closed photoacoustic cell (CPC) and piezoelectric (PZT) detections. In each case, the photoacoustic (PA) signals were found to be linear up to the laser power of 16 m W. In comparison, the power meter responsivity for CPC detection always higher than OPC and followed by PZT detection. Finally, the thermal lens technique was used to determine the thermal diffusivity of liquid samples. The phenomenon of thermal lensing is due to the refractive index change with temperature in a liquid medium causes by the periodic photothermal heating. The change of the refractive index will turn the heated medium into a lens. By measuring the time dependence of the laser intensity change after passed though the thermal lens, the thermal diffusivity of the sample can be obtained. In this work, the measurements were carried out for various solvents, fuel, palm oils and chitosan at different concentration. It was found that the thermal lens technique was suitable for measuring thermal diffusivity value of liquids in the range of (9.09 x 10-4 - 12. 1 X 10-4) cm2/s.